OP0295 N-LINKED GLYCANS IN THE VARIABLE DOMAIN OF ACPA-IGG IN THE DEVELOPMENT OF RHEUMATOID ARTHRITIS. (June 2019) - Hafkenscheid, Lise; de Moel, Emma C.; Smolik, Irene; Meng, Xiaobo; Tanner, Stacy; Jansen, Bas C.; Bondt, Albert; Wuhrer, Manfred; Huizinga, Thomas; Toes, Rene; El-Gabalawy, Hani; Scherer, Hans Ulrich
Abstract : Background: Anti-citrullinated protein antibodies (ACPA) are disease-specific biomarkers in rheumatoid arthritis (RA). Recently, we described that more than 90% of ACPA-IgGs harbour N-linked glycans in the antibody variable (V) domain. The corresponding N-glycosylation sites in the amino acid backbone of ACPA V-regions result from somatic hypermutation, a T cell-dependent process. Notably, both genetic evidence and data obtained from the analysis of serum ACPA indicate that T-cells drive the maturation of the ACPA-response prior to the onset of arthritis. Objectives: We investigated whether ACPA-IgG carry V-domain N-glycans prior to the development of arthritis and whether the occurrence of such glycans predicts the transition from pre-disease autoimmunity to overt RA. Methods: Two independent sets of serum samples were obtained from RA patients and from ACPA-positive first-degree relatives (FDR) of RA-patients (n=126) of an Indigenous North American (INA) population with high incidence rates of ACPA-positive RA. These samples comprised cross-sectional and longitudinal samples of individuals who did or did not transition to inflammatory arthritis. Serum ACPA-IgG were affinity-purified and subjected to enzymatic glycan release and UHPLC-based glycan analysis. Results: ACPA-IgG V-domain glycosylation could be detected in RA patients and in FDR of RA patients. In both datasets, FDR-derived ACPA-IgG displayed markedly lower levels of V-domain glycans (<50%) compared to ACPA-IgG from RA-patients. Notably, FDRs that later developed RA showed extensive V-domain glycosylation before the onset of arthritis. Moreover, the degree of ACPA-IgG V-domain glycosylation in FDRs was strongly associated with future development of RA (HR: 6.07 [95% CI: 1.46-25.2]; p=0.013). Conclusion: Glycosylation of the ACPA-IgG V-domain can be detected prior to the onset of disease. Extensive glycosylation is present in a subset of predisposed FDRs of INA RA patients. The presence of this feature substantially increases the risk of RA development. These observations fit well with a pivotal role for T cells in the selection and expansion of ACPA-expressing B cells, possibly by facilitating the introduction of N-glycosylation sites in ACPA-IgG V-domains. Moreover, glycosylation of the ACPA-IgG V-domain represents a predictive marker for RA development in ACPA-positive individuals and may serve to better time and target preventive therapeutic interventions. Disclosure of Interests: Lise Hafkenscheid: None declared, Emma C. de Moel: None declared, Irene Smolik: None declared, Xiaobo Meng: None declared, Stacy Tanner: None declared, Bas C. Jansen: None declared, Albert Bondt: None declared, Manfred Wuhrer: None declared, Thomas Huizinga Consultant for: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, GSK, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience Inc., Nycomed, Boeringher, Takeda, Zydus, Epirus, Eli Lilly, Rene Toes Grant/research support from: Sanofi, Hani El-Gabalawy: None declared, Hans Ulrich Scherer Grant/research support from: Sanofi, BMS